Circular economy performance assessment methods: A systematic literature review. (20th August 2019) - Sassanelli, Claudio; Rosa, Paolo; Rocca, Roberto; Terzi, Sergio
Abstract: The depletion of resources and the downgrading of the environment, driven by globalization and consumerism phenomena, is worldwide pushing the interest on the Circular Economy (CE) concept. Supposed to substitute the end-of-life notion with restoration and closed-loop product lifecycles, CE wants to eliminate wastes, retain the value embedded into products and materials, foster the use of renewable energies and eliminate toxic chemicals. However, the measurement and assessment of circularity performances are not yet a common practice in companies. To this aim, the paper wants to detect, through a systematic literature review, which are the existing CE performance assessment methods proposed in literature and, based on key findings, develop a positioning framework for measuring and assessing the circularity degree of a company.